The urban transport crisis in emerging economies - Pojan, Dorina (AESOP, 2016)
The prosed round table will discuss urban transport issues, policies, and initiatives in some of the world’s major emerging economies: Brazil, China, Colombia, India, Indonesia, Iran, Mexico, Nigeria, Russia, South Africa, Turkey, and Vietnam. The round table will aim to include one presentation on each country, focusing on the capital and/or selected major cities. The round table will also serve as a venue to launch a new volume, entitled “The Urban Transport Crisis in Emerging Economies” which has been co-edited by the round table organizers (Dorina Pojani and Dominic Stead) and will be published by Springer in 2016 (before IV WPSC). The volume contributors will be invited to participate in the round table. Among the many “emerging economies,” as defined by think tanks, investment firms, and international organizations, the countries listed above share a range of similar characteristics. They all have: (a) high urbanization rates (including megacities) relative to “developed” countries due to mass rural-urban migration and/or high birth rates; (b) dynamic urban development processes, led mostly by the private sector, with high construction levels; (c) extensive urban sprawl (including decaying large housing estates) and middle and upper class suburbanization; (d) segregated communities (e.g. gated communities for the rich and the middle classes); (e) chaotic traffic patterns, with high car and motorcycle use, and high environmental pollution; (f) rapidly growing motorization; and (g) informality and/or corruption in the formal planning system. In the past decade, studies have analyzed transport issues in individual cities in these countries.
Proceedings of the IV World Planning Schools Congress, July 3-8th, 2016 : Global crisis, planning and challenges to spatial justice in the north and in the south